Pengembangan E-Modul Dilengkapi Quick Respon (QR) Code Pada Materi Transport Dan Pertukaran Zat Pada Manusia Fase F SMA/MA - Afma, Yuwinda Isnainni; Afza, Aulia; Susanti, Diana (Jurnal Pendidikan, Sains Dan Teknologi, 2024)
This research aims to produce e-module biology teaching materials equipped with valid and practical Quick Response (QR) Codes for Phase F SMA/MA students. The research conducted is a development research (Developmental Research). The model applied is the 4-D model consisting of 4 stages, namely define, design, develop, and disseminate, due to limited costs and time, the research conducted only up to the develop stage. Data were obtained directly from 5 validators. The subjects of the study were 2 biology teachers and 36 students of class XII Phase F SMA Negeri 2 Solok. Based on the validity value by the strategy, media, and material validators, the criteria were very valid with an average value of 90.12%. The results of the practicality test conducted by teachers and students obtained very practical criteria with an average of 92.2% by teachers and 96.7% by students. Based on the research that has been conducted, teaching materials in the form of e-modules have been produced on the material on transport and exchange of substances in humans for Phase F of SMA/MA which are very valid and very practical.